2020
DOI: 10.1155/2020/4653204
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of NSGA-II and NSGA-III for Autoscaling Parameter Sweep Experiments in the Cloud

Abstract: The Cloud Computing paradigm is focused on the provisioning of reliable and scalable virtual infrastructures that deliver execution and storage services. This paradigm is particularly suitable to solve resource-greedy scientific computing applications such as parameter sweep experiments (PSEs). Through the implementation of autoscalers, the virtual infrastructure can be scaled up and down by acquiring or terminating instances of virtual machines (VMs) at the time that application tasks are being scheduled. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…NSGA-III was developed in 2014 for solving multi-objective optimization problems. It is an extension of the popular NSGA-II to handle many objective functions and improve the distribution and diversity of solutions [71,72]. Figure 4 summarizes the mechanisms in NSGA-III.…”
Section: Methods For Solving Multi-objective Optimization Problem (Moop)mentioning
confidence: 99%
“…NSGA-III was developed in 2014 for solving multi-objective optimization problems. It is an extension of the popular NSGA-II to handle many objective functions and improve the distribution and diversity of solutions [71,72]. Figure 4 summarizes the mechanisms in NSGA-III.…”
Section: Methods For Solving Multi-objective Optimization Problem (Moop)mentioning
confidence: 99%
“…The NSGA-II and NSGA-III are two widely applied variants of the GA. Compared to NSGA-II, NSGA-III has exhibited outstanding F I G U R E 1 Flowchart for the proposed integration framework performance in generating evenly distributed Pareto fronts in the objective space and is more suitable to address problems with more than two conflicting objectives (Ciro et al, 2016;Mytilinou & Kolios, 2017;Son & Kim, 2018;Yannibelli et al, 2020). Given the large number of Pareto-optimal solutions generated by NSGA-III, an additional step is required to select the ideal solution based on the final decision-makers' preferences.…”
Section: Solving Procedures Frameworkmentioning
confidence: 99%
“… 32 34 A comparative study between different evolutionary algorithms demonstrated that the nondominated sorting genetic algorithm III (NSGA-III) and the unified nondominated sorting genetic algorithm III (UNSGA-III) can achieve competitive results when compared with other approaches. 35 The performance of these algorithms was tested for an open-shop scheduling problem with resource constraints. 36 On the other hand, the multiobjective evolutionary algorithm based on decomposition (MOEAD) demonstrated superior performance in benchmark problems, such as the traveling salesman, 37 and in passive vehicle suspension optimization.…”
Section: Introductionmentioning
confidence: 99%
“…MOO algorithms permit to explore highly nonlinear systems with complex solution domains. A comparative study between different evolutionary algorithms demonstrated that the nondominated sorting genetic algorithm III (NSGA-III) and the unified nondominated sorting genetic algorithm III (UNSGA-III) can achieve competitive results when compared with other approaches . The performance of these algorithms was tested for an open-shop scheduling problem with resource constraints .…”
Section: Introductionmentioning
confidence: 99%